A missense point mutation in nerve growth factor (NGFR100W) results in selective peripheral sensory neuropathy. (November 2020) - Yang, Wanlin; Sung, Kijung; Xu, Wei; Rodriguez, Maria J; Wu, Andrew C.; Santos, Sarai A.; Fang, Savannah; Uber, Rebecca K.; Dong, Stephanie X.; Guillory, Brandon C.; Orain, Xavier; Raus, Jordan; et al.
Highlights: A NGF R100W knockin mouse model of Hereditary Sensory Autonomic Neuropathy V (HSAN V). Homozygous mutant mice showed severe, deficits in peripheral sensory structure and function. Heterozygous mutant mice developed progressive degeneration of small sensory fibers. Heterozygous mutant mice showed no apparent structural/functional changes in the brain. HSAN V is likely resulted from reduced secretion of NGF. Abstract: The R100W mutation in nerve growth factor is associated with hereditary sensory autonomic neuropathy V in a Swedish family. These patients develop severe loss of perception to deep pain but with apparently normal cognitive functions. To better understand the disease mechanism, we examined a knockin mouse model of HSAN V. The homozygous mice showed significant structural deficits in intra-epidermal nerve fibers (IENFs) at birth. These mice had a total loss of pain perception at ∼2 months of age and often failed to survive to adulthood. Heterozygous mutant mice developed a progressive degeneration of small sensory fibers both behaviorally and functionally: they showed a progressive loss of IENFs starting at the age of 9 months accompanied with progressive loss of perception to painful stimuli such as noxious temperature. Quantitative analysis of lumbar 4/5 dorsal root ganglia revealed a significant reduction in small size neurons, while analysis of sciatic nerve fibers revealed the heterozygous mutant mice had no reduction in myelinated nerve fibers. Significantly, the amount of NGF secreted from mouse embryonic fibroblasts were reduced from both heterozygous and homozygous mice compared to their wild-type littermates. Interestingly, the heterozygous mice showed no apparent structural alteration in the brain: neither the anterior cingulate cortex nor the medial septum including NGF-dependent basal forebrain cholinergic neurons. Accordingly, these animals did not develop appreciable deficits in tests for brain function. Our study has thus demonstrated that the NGF R100W mutation likely affects the structure and function of peripheral sensory neurons.